Analisis Pengulangan (REPEAT) Foto Panoramik di Instalasi Radiologi RSPAU Dr. Suhardi Hardjolukito - Azizah Azizah; Anisa Nur Istiqomah; Sofie Nornalita Dewi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Panoramic radiography is an imaging technique that plays a crucial role in dental practice, particularly in supporting the diagnosis and treatment planning process. Image quality that does not meet diagnostic standards can lead to the need for repeat imaging. The high rate of repeat panoramic imaging at the Radiology Unit of Dr. Suhardi Hardjolukito Air Force Base Hospital (RSPAU) is an indicator of the need for further study of the causal factors. The purpose of this study was to identify the causes of repeat panoramic radiography examinations, calculate the percentage contribution of each factor, assess radiographers' understanding of optimal image quality criteria, and explore appropriate strategies to reduce the frequency of repeat examinations. This study used a mixed methods approach with quantitative and qualitative descriptive approaches. Data were collected through observation, interviews, questionnaires, and documentation during August–October 2024 at the Radiology Unit of Dr. Suhardi Hardjolukito Air Force Base Hospital. The sample included 15 radiographers for the questionnaire and 3 radiographers for the interviews. An analysis of 916 panoramic radiography examinations revealed 57 repeat cases, with a rate of 6.2%. The primary factors causing repeats were machine error (57.8%), followed by positioning errors (24.5%), artifacts (10.5%), human error (5.3%), and patient movement (1.8%). Radiographers' understanding of the criteria for good panoramic images was high, with 66.7% answering all questions correctly. The primary effort implemented to reduce repeat rates is the implementation of routine quality control of equipment. The high repeat rate, exceeding national tolerance limits, indicates the need for technical and procedural improvements. Routine quality control and material refresher courses are needed to reduce repeat rates and improve patient safety.